1895 N.D. Rev. Codes 1259, Penal Code, ch. 18, § 7094 - (:unkn) unknown (My University, 1895)
Setting Spring Gun, Trap or Device. Every person who sets any spring or other gun or trap or device operating by the firing or exploding of gunpowder or any other explosive, and leaves or permits the same to be left, except in the immediate presence of some competent person, shall be deemed to have committed a misdemeanor; and the killing of any person by the firing of a gun or other device so set shall be deemed to be manslaughter in the first degree.
Keywords: TRAP GUNS